Nonopioid medications for managing opioid withdrawal in acute care settings: A scoping review. - Erstad, Brian L; Quaye, Aurora N; Hellwege, Megan E; Do, David; Kopp, Brian J (American Journal of Health-System Pharmacy, 2025)
Purpose There are hospitalized patients with chronic opioid use who will experience signs and symptoms of opioid withdrawal who were not on medications for opioid use disorder (OUD) prior to admission, do not want to start or are unable to start medications for OUD during admission, and want to limit or avoid the use of opioids. The purpose of this scoping review was to assess the potential effectiveness and safety of using non-opioid agents for managing acute opioid withdrawal in acute care settings. Methods PubMed (inception to 2024), Embase (inception to 2024), and Cochrane Library (inception to 2024) were the databases evaluated for the literature search. Bibliographies of full-text articles were reviewed for additional relevant papers. Results Twenty-eight studies evaluating nonopioid agents for managing acute opioid withdrawal were identified in the literature search. The agents could be divided into 4 broad mechanistic categories: α-adrenergic receptor agonists, N -methyl- d -aspartate (NMDA) antagonists, gamma-aminobutyric acid (GABA) modulators, and serotonergic agents. Of these drug classes, the available literature suggests the α-adrenergic receptor agonists clonidine and lofexidine have the best evidence of efficacy as alternative agents for acute opioid withdrawal, although the majority of studies comparing such agents to opioids for opioid withdrawal were conducted well before the rise in synthetic opioid overdose deaths and have other methodologic issues that limit firm conclusions concerning efficacy and, particularly, safety. Conclusion For the nonopioid alternative agents that have been studied for acute opioid withdrawal, there is more evidence supporting the efficacy of α-adrenergic receptor agonists as opposed to NMDA antagonists, GABA modulators, or sertonergic agents; however, more research is needed regarding the efficacy and safety of nonopioid alternatives for acute opioid withdrawal in order to better guide clinical decision-making.